Paclitaxel, epirubicin, and carboplatin in advanced or recurrent endometrial carcinoma: A Hellenic Co-operative Oncology Group (HeCOG) study - Papadimitriou, C.A.; Bafaloukos, D.; Bozas, G.; Kalofonos, H.; Kosmidis, P.; Aravantinos, G.; Fountzilas, G.; Dimopoulos, M.-A. (Gynecologic Oncology, 2008)
Objective: Taxanes, anthracyclines, and platinum compounds represent the chemotherapeutic agents with the greatest activity in metastatic endometrial carcinoma. We administered the combination of paclitaxel, epirubicin and carboplatin to patients with metastatic or recurrent carcinoma of the endometrium to evaluate its activity and to define its toxicity. Methods: Sixty-three consecutive patients were treated on an outpatient basis with epirubicin 50 mg/m2, followed by paclitaxel 150 mg/m2, administered intravenously over a 3-h period. Subsequently, the patients received carboplatin at AUC of 5. The chemotherapy was repeated every 3 weeks with granulocyte colony-stimulating factor (G-CSF) support for a maximum of six courses. Results: Response was assessed among 56 eligible patients. Thirty-six (63.2%) patients achieved objective clinical response (95% CI, 50.6-75.7%) including 14 (24.6%) complete and 22 (38.6%) partial responses. The median duration of response was 7.9 months, and the median times to progression and survival for all patients were 7.8 and 13.8 months, respectively. Grade 3 or 4 neutropenia occurred in 9 (15.5%) patients but only 3 episodes of neutropenic fever were encountered. Grade 2 or 3 neurotoxicity was observed in 19% of patients. Two patients died of sudden cardiac death 10 and 14 days after the administration of the first chemotherapy cycle, respectively, but these deaths were not clearly treatment related. Conclusions: The combination of paclitaxel, epirubicin and carboplatin with G-CSF support appears active in patients with metastatic or recurrent carcinoma of the endometrium. © 2008 Elsevier Inc. All rights reserved.
Keywords: Carboplatin; Epirubicin; Metastatic endometrial cancer; Paclitaxel